The Effect of Active Packaging Film Containing Rosemary Extract on the Quality of Smoked Rainbow Trout (Oncorhynchus mykiss) - Coban, Ozlem Emir; Can, Ozlem Pelin (Taylor & Francis Inc, 2013)
In this study, the effect of active packaging film containing rosemary extract on the quality of smoked rainbow trout (Oncorhynchus mykiss) was investigated. Smoked rainbow trout was packaged in both low density polyethylene film containing rosemary extract (sample A = 0.5% and sample B = 1%) and polyethylene film without rosemary extract (control) and stored at 4 degrees C. Samples were analyzed for 63 days to determine their chemical quality and sensory attributes. The peroxide value, free fatty acid, totox, and thiobarbituric acid content were significantly higher in the control samples than in samples A and B during storage. The results indicate that lipid oxidation is affected by active packaging film containing rosemary extract. In addition, rosemary extract has been shown to have a positive effect on the sensory quality of smoked rainbow trout (p < 0.05).
Keywords: rosemary extract; natural antioxidant; Oncorhynchus mykiss; active packaging; lipid oxidation